2008
DOI: 10.1105/tpc.108.062919
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of a Protein Disulfide Isomerase, PDIL2-1, Delays Embryo Sac Maturation and Disrupts Pollen Tube Guidance inArabidopsis thaliana

Abstract: Pollen tubes must navigate through different female tissues to deliver sperm to the embryo sac for fertilization. Protein disulfide isomerases play important roles in the maturation of secreted or plasma membrane proteins. Here, we show that certain T-DNA insertions in Arabidopsis thaliana PDIL2-1, a protein disulfide isomerase (PDI), have reduced seed set, due to delays in embryo sac maturation. Reciprocal crosses indicate that these mutations acted sporophytically, and aniline blue staining and scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 50 publications
1
62
0
1
Order By: Relevance
“…BiP, CRT, and members of the PDI/PDIL family are frequently referred to as ER-lumen resident protein chaperones (Galat and Metcalfe, 1995;Jelitto-Van Dooren et al, 1999;Frand et al, 2000;Wu et al, 2010a). For a number of years, the definition of these proteins as ER residents has been questioned (Turano et al, 2002), and while BiP, CRT, and several of the PDI members identified in this study have been localized by fluorescent protein to the ER (Eubel et al, 2008;Wang et al, 2008), it is interesting that localization by MS suggests a more ubiquitous distribution (Heazlewood et al, 2004;Jaquinod et al, 2007;Marmagne et al, 2007;Mitra et al, 2009). It has now been conclusively demonstrated that BiP and CRT cycle between the ER and cis-Golgi and that both BiP and PDI1-1 are transported to lytic vacuoles via the Golgi apparatus (Pimpl et al, 2006;Ondzighi et al, 2008).…”
Section: Untangling the Endomembranementioning
confidence: 63%
“…BiP, CRT, and members of the PDI/PDIL family are frequently referred to as ER-lumen resident protein chaperones (Galat and Metcalfe, 1995;Jelitto-Van Dooren et al, 1999;Frand et al, 2000;Wu et al, 2010a). For a number of years, the definition of these proteins as ER residents has been questioned (Turano et al, 2002), and while BiP, CRT, and several of the PDI members identified in this study have been localized by fluorescent protein to the ER (Eubel et al, 2008;Wang et al, 2008), it is interesting that localization by MS suggests a more ubiquitous distribution (Heazlewood et al, 2004;Jaquinod et al, 2007;Marmagne et al, 2007;Mitra et al, 2009). It has now been conclusively demonstrated that BiP and CRT cycle between the ER and cis-Golgi and that both BiP and PDI1-1 are transported to lytic vacuoles via the Golgi apparatus (Pimpl et al, 2006;Ondzighi et al, 2008).…”
Section: Untangling the Endomembranementioning
confidence: 63%
“…A number of additional genes and proteins have been postulated to play a role in funicular and micropylar PT guidance in Arabidopsis [28][29][30][31][32][33]. However, the majority of the genes seem to be required for PT growth, and FG maturation thus plays a more indirect or no role for PT guidance.…”
Section: Signalling In Gametophytic Pt Guidancementioning
confidence: 93%
“…Insertional inactivation of the PDI5 gene hastens the onset of programmed cell death in embryos, preventing seed development. Alternatively, PDI11 is a strict ER resident that assists embryo sac maturation and pollen tube direction (Wang et al, 2008), but proteins interacting with PDI11 have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%